Direction of Causality between Financial Development and Economic Growth Evidence from Egypt - El Banna, lslam Nohamed; Abdelsalam, Mamdouh AbdelmouIa M. (جامعة الزقازيق - كلية التجارة, 2018)
The connection of the causality between capital financial market development and economic growth has received much attention throughout last years. The long-run relationship between the level of financial development and economic performance is generally recognized and accepted (Goldsmith, 1969; King and Levine, 1993). The origin of these types of investigations is found in the research conducted by Schumpeter (1934). He argues that financial intermediaries are important for innovation and development .The current study derives its motivation from the notion that the finance-growth discourse should be narrowed down to individual countries. Therefore this study provides an empirical assessment relating to the linkage between financial development and economic growth in Egypt in the long run and in the short run. The study uses the model of Vector Error Correction Model (VECM) comprising GDP growth rate, some selected financial variables. The study found that GDP is negatively and significantly affected by both the real interest rate and the real exchange rate. Real interest rate is responded positively by variations in GDP. In addition, domestic credit as a percentage of GDP is significantly affected by GDP and exchange rate.
لقيت العلاقة السببية بين تطور أسواق المال والنمو الاقتصادي الكثير من الاهتمام من جانب الباحثين، طوال السنوات الماضية، وانصب اهتمام الدراسات السابقة على العلاقة طويلة المدى بين مستوى تطور النظام المالي، والأداء الاقتصادي، وهي العلاقة التي بدت معترف بها ومقبولة بشكل عام (جولد سميث، ١٩٦٩؛ كينغ وليفين، ١٩٩٣). وترجع بدايات اهتمام الباحثين بهذه العلاقة إلى البحث الذي أجراه (1934) Schumpeter، حيث يرى بأن الوسطاء الماليين لهم دور أساسي في عملية الابتكار والتطوير، ثم تبعه الكثير من الباحثين من خلال دراسات تطبيقية متنوعة، توصلت إلى نتائج متباينة بخصوص طبيعة تلك العلاقة والاتجاهات السببية بينهما، وتستمد الدراسة الحالية أهميتها من الفكرة القائلة بأن العلاقة السببية بين التطور المالي والنمو الاقتصادي مرتبطة اساسا بالظروف المحلية ومن ثم فإن الدراسات التطبيقية على الدول المنفردة تحظى بأولوية. لذلك تقدم هذه الدراسة تقييما تطبيقيا يتعلق بالربط بين التطور المالي والنمو الاقتصادي في مصر على المدى الطويل وعلى المدى القصير. تستخدم الدراسة نموذج "تصحيح الخطأ المتجه (VECM) الذي يتضمن معدل نمو الناتج المحلي الإجمالي، وبعض المتغيرات المالية المختارة. وتوصلت الدراسة إلى أن الناتج المحلي الإجمالي يتأثر سلبا وبصورة كبيرة بكل من معدل الفائدة الحقيقي وسعر الصرف الحقيقي. ومن ناحية أخرى تبين الدراسة أن سعر الفائدة الحقيقي ارتبط بعلاقة موجبة بالتغير في الناتج المحلي الإجمالي، وتبعه في ذلك كلا من الائتمان المحلي وسعر الصرف، مما يؤكد على أهمية دور التطور المالي في إحداث التنمية.
Keywords: الأسواق المالية -- التنمية الاقتصادية -- النمو الاقتصادى -- السياسة النقدية -- مصر